FORMULASI OBAT KUMUR EKSTRAK DAUN BINAHONG DAN KAYU MANIS TERHADAP BAKTERI Streptococcus mutans - Rakhmayanti, Regia Desty; Nur Aisiyah, Astri Dewi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Dental caries is a disease in the oral cavity, this disease can be prevented by using mouthwash. Plants that have antibacterial activities include binahong leaves and cinnamon . This study aims was to determine the quality and antibacterial activity of mouthwash that containing against Streptococcus mutans. Mouthwash preparations was carried out by various concentrations of binahong leaves and cinnamon extract. Preparation F0 is without extract, F1 (6%:3%), F2 (7%:3%), F3 (8%:3%). The organoleptic test results of the mouthwash was clear brown in color and had a distinctive aroma of binahong leaves and cinnamon. The pH test results were F0 6.529±0.16; F1 5.256±0.004; F2 5.333±0.002; and F3 5.373±0.003. The density measurements results were F0 1.0766±0.04852; F1 1.0309±0.00056; F2 1.0317±0.00032; and F3 1.0364±0.00325. The viscosity measurement results were F0 3.170±0.02; F1 3.203±0.02; F2 3.323±0.01; and F3 3.380±0.02. The antibacterial activity test result were F0 0.00 mm; F1 6.39±0.03 mm; F2 7.29±0.06 mm; F3 8.89±0.07 mm; negative control (distilled water) 0.00 mm; and positive control (chlorhexidine 0.2%) 21.35±0.10 mm. The preparation fulfilled the physical quality parameter requirements of mouthwash and has antibacterial activity against Streptococcus mutans.